The Perception of Water Quality and Related Diseases in Rural Areas of the Department of Tiassalé, Côte d’Ivoire, West Africa - Ouattara, Adidjatou; Meite, Alassane; Dally, Theodor; Ouattara, Howele; Kati-Coulibaly, Seraphin (European Scientific Journal, ESJ, 2019)
One of critical public health concerns in many developing countries today is water quality and the risks associated with waterborne diseases. Many research works that have studied about factors contributing to water pollution have not considered the perception on drinking water quality and health risk in the rural area of the department of Tiassalé. This study therefore focuses on evaluating the level of perception of households living in the rural area of Tiassalé. The study data were collected through interviews from a total of 600 respondents with structured questionnaire. The majority of the respondents (78.2%) used water from hand dug wells for drinking purpose. According to 77.7 % of respondents, water from the wells was safe for drinking. Around 9.3% had a degree of knowledge about the sources of well water contamination. Majority of the respondents (87.3 %) did not treat their water. About 80% of residents mentioned that they had not experienced any negative effects from drinking the well water. Variables associated with perception of drinking water quality included educational status, use of at least one method of water treatment, and awareness of health risks of drinking contaminated water. The results of this study indicated that knowledge on water quality and health risks were poor.